Fermentation strategies for sorghum grain applications - López Galdamez, Victoria Alejandra (My University, 2026)
Sorghum is a cereal grain with significant potential for food applications due to its composition, gluten-free nature, and high antioxidant content. However, its use remains limited by intrinsic factors such as condensed tannins, phytic acid, and enzyme inhibitors, which can reduce nutrient availability and functionality. Fermentation represents a promising strategy to modify these properties and enhance sorghum value through microbially driven transformations. The objective of this research was to evaluate fermentation strategies to expand the use of sorghum grains using both submerged and solid-state systems, and to determine how sorghum variety and fermentation conditions influence microbial dynamics. To address this objective, three complementary studies were conducted. In the first study, three whole sorghum grain varieties, sumac, waxy, and white, were used as substrates for kombucha fermentation and evaluated over 7 days by monitoring pH, soluble solids (°Brix), microbial counts, and microbial community composition using shotgun metagenomic sequencing. All treatments exhibited a significant decrease (p<0.05) in pH and °Brix, along with an increase in microbial population, indicating active fermentation. Metagenomic analysis showed that sorghum-based fermentations maintained microbial profiles similar to those of the starter culture, indicating that sorghum can support kombucha fermentation while preserving its characteristic microbiota. To further assess potential functional effects, the second study evaluated the effects of sorghum kombucha consumption in an obesity intervention model using Ossabaw pigs. Animals received either sorghum kombucha or an isocaloric tea control, and fecal samples were analyzed for Enterobacteriaceae counts and microbial community composition. Kombucha supplementation significantly reduced Enterobacteriaceae shedding (p < 0.05) across body types. However, beta diversity analysis indicated that host body type had a greater influence on microbial community composition than treatment, highlighting the importance of host-related factors in shaping microbiome responses. In the third study, lactic acid bacteria-mediated solid-state fermentation was used to ferment three whole sorghum grain varieties (i.e., black, sumac, and white), under different moisture conditions and inoculum treatments. Fermentation resulted in significant reductions in phytic acid and pH (p < 0.05), along with increases in microbial populations. In vitro protein digestibility improved significantly in selected treatments, particularly in black and sumac sorghum varieties. The observed effects were influenced by sorghum variety, inoculum type, and moisture level. Collectively, these findings demonstrate that fermentation can be an effective strategy to enhance sorghum functionality and broaden its applications. Sorghum supported fermentation in both submerged and solid-state systems. However, fermentation dynamics were strongly influenced by substrate characteristics and processing conditions, highlighting the need for tailored fermentation approaches. These findings provide a foundation for developing targeted strategies and support the use of sorghum as a versatile ingredient in functional food applications.
Keywords: Kombucha; Swine; Lactic acid bacteria; Solid state fermentation; In vitro digestion